2017
DOI: 10.1016/j.celrep.2017.10.010
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Translatome Profiling in Spinal Muscular Atrophy Reveals a Role for SMN Protein in Ribosome Biology

Abstract: SummaryGenetic alterations impacting ubiquitously expressed proteins involved in RNA metabolism often result in neurodegenerative conditions, with increasing evidence suggesting that translation defects can contribute to disease. Spinal muscular atrophy (SMA) is a neuromuscular disease caused by low levels of SMN protein, whose role in pathogenesis remains unclear. Here, we identified in vivo and in vitro translation defects that are cell autonomous and SMN dependent. By determining in parallel the in vivo tra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
120
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(129 citation statements)
references
References 80 publications
(102 reference statements)
8
120
1
Order By: Relevance
“…However, splicing defects in SMA models are found throughout different tissues, suggesting that SMA pathogenesis relies on additional RNA‐related pathways occurring in neurons. In fact, SMN is a multifunctional protein involved in ribosomal RNA biogenesis, processing of mRNAs, mRNA transport, and translation control …”
Section: Introductionmentioning
confidence: 99%
“…However, splicing defects in SMA models are found throughout different tissues, suggesting that SMA pathogenesis relies on additional RNA‐related pathways occurring in neurons. In fact, SMN is a multifunctional protein involved in ribosomal RNA biogenesis, processing of mRNAs, mRNA transport, and translation control …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a potential role for free RPs in the maintenance of ribosomes in axons has been implicated in a mouse model of spinal muscular atrophy (SMA) (Bernabo et al, 2017).…”
mentioning
confidence: 99%
“…The depletion of the survival motor neuron (SMN) protein, an RNA-binding protein that associates with RP-coding mRNAs (Rage et al, 2013), caused a significant decrease in translation levels of RP-coding mRNAs in mouse motor neuron axons. Although the causal relationship remains uncertain, SMN depletion also leads to a 27% reduction in the number of ribosomes in the axons (Bernabo et al, 2017). These studies prompted us to ask whether axonal ribosomes incorporate locally synthesized RPs to support and/or modify the ribosome function far from the cell body although the limited amount of axonal material make this a technically challenging question to address.…”
mentioning
confidence: 99%
“…In line with our findings, previous studies have reported apparently independent activities of SMN complex members. For example, SMN1 regulates ribosome biology and motor neuron growth 5,44,45 , SMN1's function in motor neurons appears to be independent of snRNP biosynthesis 46 , and SMN1 has a specific role in axonal mRNA regulation and axonogenesis 7,8 . Furthermore, GEMIN3, an RNA helicase, is involved in cell proliferation and microRNA regulation of signal transduction 9 .…”
Section: Discussionmentioning
confidence: 99%
“…The SMN complex consists of nine proteins, however the majority of research on the complex has focused on the characterization of SMN1 and its role in SMA. In addition to its role in the SMN complex, SMN1 plays a role in many other biological processes, including axon growth, mRNA transport, ribosome biology, translational control, and maintaining intracellular homeostasis [5][6][7][8] . Although there is some evidence showing that other SMN complex members, such as GEMIN3 and GEMIN5, also have functions independent of the SMN complex [9][10][11][12] , it remains largely unknown how the other SMN complex members relate to SMA, and whether other members have functions beyond the SMN complex.…”
Section: Introductionmentioning
confidence: 99%